«Women-actors». Prime notizie sulle attrici inglesi della Restaurazione - Barbieri, Maria Chiara (Drammaturgia, 2020)
The essay traces the complex but rapid process of reopening the theaters and reorganizing the dramatic London companies after a nearly twenty years’ interruption of spectacular activities. In 1660, as soon as Charles II returns to the throne, he orders the immediate resumption of theatrical performances, which for the first time will see the female characters acted by women. Women who are not yet called actresses, but ‘women actors’ like the actors who used to perform the female parts before the theatres’ closure in 1642. At first their colleagues do not like the innovation which, instead, is quickly welcomed by the public. Although almost without training, most of the actresses who first tread the stage will be able of making theatre a profession, some even to excel in it.